Competitive anxiety and its impact on concentration levels in sports competitions among athletes with special needs. - Laoucine, slimane; mouafek, saleh (sports creativity, 2025)
Sport is an important part of the history of nations. It has played a significant role in many international relations, and many countries have raised their flags thanks to their athletes' achievements. As they say, sport has become essential in our daily lives. "A sound mind in a sound body" has become a common motto in everyday sporting life (1). A healthy person experiences joy, sadness, anger, hatred, love, and rebellion, but only within the limits of the stimuli they encounter. Some stimuli exceed an individual's ability to adapt, such as those experienced by groups deprived of one of the blessings God has bestowed upon us, like the hearing, physical, and intellectually disabled, etc. Perhaps what hinders this group is their interaction with the rest of society, as they are often targeted by negative attitudes and discriminatory practices, leading to isolation and making them vulnerable to various pressures, including psychological pressures, which are a common occurrence in life. Psychology is one of the most important sciences that cannot be dispensed with in the field of sports. It provides theories that help prepare athletes psychologically for athletic competitions so they can perform at the required level (2). The concept of disability has changed significantly in recent times. Whereas people once viewed it as a permanent impairment, whether mental or physical, today a person with a disability is considered an ordinary human being with their own specific needs. Anxiety, especially competitive anxiety, is one of the most important phenomena that plays a significant role in affecting the performance of runners. A runner may experience anxiety throughout their athletic career in general and during competition in particular. The degree of individual adaptation varies depending on the difficulties encountered. Each athletic skill requires an optimal level of preparation to achieve maximum performance. Athletes face many situations directly related to anxiety, as anxiety has a direct impact on an individual's behavior and, consequently, on their performance level. Understanding all aspects related to anxiety allows us to educate and nurture athletes on sound principles that enable them to deal with different situations, whether in the athletic field or in public life, with natural adaptation and preparation, far removed from the level of anxiety that affects behavior and performance, leading to frustration and conflict among athletes in general and athletes with special needs in particular.